Design and Development of Urban roads in Developing Countries - Wadhwani, Jitendra (PREPARE@u® | IEI Conferences, 2021)
Roads are one of the most important components for socio-economic development of any part of the world. Construction of New roads and improvement of the existing road is the key to expand development of small town and bring them to their full potential. Development of major towns and capitals was emphasised which indirectly creates chaos, encouraged human migration, scarcity of basic utilities. Lack of focus and low investments has suppressed small towns and failed in bringing out the full potential of available infrastructure assets and human resources. In this paper, development of small towns in Indian subcontinent and associated challenges are highlighted. In recent years, India-a developing country has realized need of small-town development and initiated “Smart City Mission” to bring the additional investment in urban areas in different states of the country. Road development and mobility are the key component of this mission. The main challenge with road design in small town are unorganized existing infrastructure, competency of technical staff with municipal corporation, construction quality of local contractors, lack of standards, specifications and guidelines, trust deficit of public in government works, Policies, SOPs, Law, order and enforcement issues etc. To overcome above challenges, it is important to bring the sound policies, deal with competency issues of engineers and win the trust of public or end users. For a good road development, a good and flawless design is utmost important. Improvement of existing roads and utilities such as storm, sewer and electric lines play important role in road design and needs to be considered as an integral system instead of designing these components separately. This paper provides the brief of the planning and design elements of urban roads development in small towns, issues & challenges faced by stakeholders and way forward. It has been observed that existing infrastructure of small town is unorganized, unplanned and mismanaged. To overcome these issues and bringing new development, keeping the town operational, detailed planning and good design is required before start of any ground activities. Paper brings the steps to review existing infrastructure, investigations required, stakeholder engagement, design parameters and components, quantity measurements and technical input to tender documents.